Đáp án+Giải thích các bước giải:
`(2019a+b+c+d)/a=(a+2019b+c+d)/b=(a+b+2019c+d)/c=(a+b+c+2019d)/d`$\\$`=>(2019a+b+c+d)/a-2019=(a+2019b+c+d)/b-2019=(a+b+2019c+d)/c-2019=(a+b+c+2019d)/d-2019`$\\$`=>(a+b+c+d)/a=(a+b+c+d)/b=(a+b+c+d)/c=(a+b+c+d)/d(***)`
`**Nếu\ a+b+c+d=0=>a+b=-(c+d)=>(a+b)/(c+d)=-1`$\\$`**Nếu\ a+b+c+d=0=>b+c=-(a+d)=>(b+c)/(a+d)=-1`$\\$`**Nếu\ a+b+c+d=0=>c+d=-(a+b)=>(c+d)/(a+b)=-1`$\\$`**Nếu\ a+b+c+d=0=>d+a=-(b+c)=>(d+a)/(b+c)=-1`$\\$`=>M=-4`
`**Nếu \ a+b+c+d\ne0`$\\$`Từ\ (***)=>a=b=c=d=>(a+b)/(c+d)=(b+c)/(d+a)=(c+d)/(a+b)=(d+a)/(b+c)=1`$\\$`=>M=4`